'To tweet or not to tweet?' A study of the use of Twitter by scholarly book publishers in Social Sciences and Humanities. Issue 3 (August 2021) - Wang, Yajie; Hou, Haiyan; Hu, Zhigang
Highlights: Twitter is a popular and efficient channel for disseminating scientific outputs, it seems to be an acceptable publisher engagement rate, but still the minority. Only 12% of the surveyed books were mentioned by their publisher Twitter accounts on Twitter from 2014 to 2018. More and more publishers are participating in Twitter book promotion. Compared with some traditional publishing giants, media-small publishers have higher Twitter engagement. Publisher play an important role in the scientific communication process on Twitter, books were mentioned by their publishers on Twitter get more tweets than books were mentioned by non-publishers. Abstract: Publishers might believe the use of Twitter will help promote their scholarly books. In this study, we analyzed 18, 691 books indexed by the Book Citation Index (BKCI) in the Social Sciences and Humanities, published between 2014 and 2018, and proposed two indicators describing the Twitter engagement of publishers: relative coverage and relative receptivity . The results show significant disciplinary and year differences in publishers' Twitter engagement For instance, in all 10 disciplines, small and medium-sized publishers generally prefer to promote their books (high relative coverage) on Twitter, but the majority of publishers have low relative coverage in these 5 years. In addition, results show that books mentioned by their publishers' Twitter accounts get significantly higher Twitter mentions (high relative receptivity) as compared to books mentioned by non-publisher' Twitter accounts. The results suggest that scholarly book publishers should engage in social media activity to increase Twitter mentions and visibility of their books.